Effect of Oral Coadministration of Ascorbic Acid with Ling Zhi Preparation on Pharmacokinetics of Ganoderic Acid A in Healthy Male Subjects: A Randomized Crossover Study - Patcharanee Tawasri (2018)
© 2016 Patcharanee Tawasri et al. The objective of this randomized, open-label, single-dose, two-phase crossover study was to determine the effect of ascorbic acid on pharmacokinetics of ganoderic acid A, an important biologically active triterpenoid compound with anticancer activities, following oral administration of water extract of fruiting bodies of Ling Zhi in 12 healthy male subjects. Each subject was randomized to receive either one of the two regimens: (1) a single dose of 3,000 mg of the Ling Zhi preparation or (2) a single dose of 3,000 mg of the Ling Zhi preparation in combination with 2,500 mg of ascorbic acid. After a washout period of at least two weeks, subjects were switched to receive the alternate regimen. Blood samples were collected in each phase immediately before dosing and at specific time points for 8 hours after dosing. Plasma ganoderic acid A concentrations were quantified using liquid chromatography-mass spectrometry (LC-MS). The pharmacokinetic parameters analyzed were maximal plasma concentration (C m a x), time to reach peak concentration (T m a x), area under the plasma concentration-time curve (A U C), and half-life (t 1 / 2). An oral coadministration of ascorbic acid with Ling Zhi preparation did not significantly alter the pharmacokinetic parameters of ganoderic acid A in healthy male subjects.